Vocação hidrogeológica do aquífero serra grande, nos Estados do Ceará e Piauí, e do aquífero cabeças, no Estado do Piauí, através de modelagem em sig. - Leite, Carlos Eduardo Sobreira (2019)
This work presents an assessment of the Hydrogeological Vocation, through scenarios, of the Serra Grande Aquifer, in the States of Piauí and Ceará, and of the Cabeças Aquifer, in the State of Piauí, based on their sediment volumes and the specific capacities of tubular wells. The research began with the survey and integration of the main information on geology, structure and hydrogeology to a GIS database, available throughout the Parnaíba Basin. In total, 6,342 points were collected and organized with information on subsurface geology that were subsequently criticized and elected the ones used in this work, being 190 points for the Serra Grande Aquifer and 232 points for the Cabeças Aquifer. Once the data were organized the stratigraphic isopic and stratigraphic hydroisopic curves were constructed for both aquifers, through a new methodological proposal of Mathematical Modeling with Refinement and subsequent Qualitative Adjustment - MoMaRAQ in GIS. The maximum thicknesses after the adjustment reached values for the Serra Grande Aquifer of 754.6m (hydroisopic) and 819m (isopic) while for the Cabeças Aquifer the values were 406,7m (hydroisopic) and 563,6m (isopic) . Once the curves were generated, the sediment volumes of each aquifer were calculated, resulting in a total of 80,949km3 (isopic) and 75,634.16km3 (hydroisopic) aquifers for the Serra Grande Aquifer, while for the Aquifer Heads the volumes were 39,423 , 98km3 (isopic) and 34,355.42km3 (hydroisopic). Specific capacities were determined from results of pumping tests on tubular wells that distinctly capture Serra Grande Aquifer (479 wells) and Cabeças Aquifer (464 wells). Four scenarios of hydrogeological vocation were constructed for each of the aquifers considering their isopic and hydroisopic along with specific capacity curves for all wells and for only fully penetrating wells. At the end, the top depth curves of each aquifer were generated, with the maximum depth being obtained for the Serra Grande Aquifer of 1,827m and for the Cabeças Aquifer of 877m.